Comparison of Student Achievement in Electricity Using Augmented Reality between Offline and Online Classes - Ropawandi, D.; Husnin, H.; Halim, L. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
The COVID-19 pandemic has affected education in Indonesia. The government has suggested alternatives to solve the learning problems during the pandemic. Offline and online classes were used to fulfil the various learning needs of students. This study investigated the effect of using augmented reality-assisted media in offline and online classes on student achievement amid the COVID-19 pandemic. This study used a quasi-experimental design by utilising augmented reality (AR) in each class for eight weeks. Validated test questions were used following the use of AR. According to the results of the independent t-test in the current study, student achievement from offline (n = 63, M = 74.71) and online (n = 64, M= 71.46) classes increased drastically with t = 1.994, p = 0.048. However, in terms of differences in achievement improvement between the two classes, students in offline classes had higher achievement compared to those in online classes. Thus, it can be concluded that student achievement in Physics has improved with the help of augmented reality-assisted media amidst the COVID-19 pandemic, particularly through offline learning mode. This study contributes to the development of AR for future education, particularly how to enhance student achievement in Physics. Future AR studies can be carried out in more classes from various regions or countries, considering that the 3D models in AR are useful to aid the learning of other subjects with abstract concepts.